Intrinsic brain network alterations in non-clinical adults with a history of childhood trauma. Issue 1 (1st January 2021) - Zhao, Haofei; Dong, Daifeng; Sun, Xiaoqiang; Cheng, Chang; Xiong, Ge; Wang, Xiang; Yao, Shuqiao
ABSTRACT: Background: Childhood trauma is a major social public-health problem worldwide. Previous literature suggests childhood trauma is associated with the development of psychiatric disorders and maladaptive behaviours later in life, but little is known about the neural basis underlying these associations. Objective: The aim of the current study was to investigate intrinsic brain network alterations in non-clinical adults with childhood trauma. Methods: Resting-state functional magnetic resonance imaging (fMRI) data were collected from 65 non-clinical adults with moderate or severe childhood trauma (CT group), according to the international demarcation criteria of the Childhood Trauma Questionnaire (CTQ), and 73 socio-demographically matched non-clinical controls without childhood trauma (no-CT group). Independent component analysis (ICA) was used to extract subnetworks of the default mode network (DMN), salience network (SN), and central executive network (CEN). Results: ICA revealed that the CT group had increased FC of the left medial prefrontal cortex (mPFC) in the anterior DMN (aDMN), increased functional connectivity (FC) of the left anterior insula in the SN, and decreased FC of the inferior parietal gyrus of the right CEN (rCEN). Compared to the controls, the CT group had decreased inter-network FCs between the SN and posterior DMN (pDMN), as well as between the pDMN and rCEN. Conclusions: Impaired FC within the three key brain networks, decreased inter-FC between SN and rCEN, and decreased inter-FC between pDMN and rCEN may reflect biomarkers of childhood trauma. HIGHLIGHTS: In this paper, we found specific FC alterations within and between three key networks in non-clinical adults with childhood trauma, which may mediate the relationship between childhood trauma and psychiatric disorders in later life.